Pengaruh Perbedaan Grade Insert Carbide terhadap Nilai Keusan Mata Pahat pada Material Baja Aisi 4140 - Chistianto, Felix; Rosehan, Rosehan; Lubis, Sobron Yamin (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
In the permesian process for making various kinds of products, various types of machines are needed, one of which is using a lathe (turning machine). In this study the method used was an experimental method, which was carried out using a conventional lathe by varying the grade of the carbide bit against AISI 4140 steel material. The results showed that the bit with grade IC9250 with a coated CVD (Chemical Vapor Deposition) content had higher coating strength. strong, so that the wear that occurs is long in the 189th minute while the IC907 grade chisel with a coated TiAlN (Titanium Aluminum Nitride) content has a weak coating strength, so the wear that occurs is faster in the 182th minute. chisel is directly proportional to the cutting time, because the rpm when the machining process is used is constant. In general, the wear that occurs on the tool eye is abrasive and abrasive wear.